The Attitude of the Head of the Family About the Prevention of Diseases with Dengue Hemorrhagic Fever - Wibowo Hanafi Ari Susanto; Isymiarni Syarif; Moh Malikul Mulki Mulki; Nordianiwati Nordianiwati; Maria Kurni Menga (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Dengue hemorrhagic fever is a disease that tends to increase the number of cases and its spread and often causes extraordinary events, even death. Until now, it is still a public health problem and can cause sufferers to die quickly. This study aims to determine the head of the family's attitude toward preventing dengue hemorrhagic fever. Research design with a cross-sectional study analytical survey approach, sample technique using purposive sampling. The results showed that most heads of households had a good attitude regarding preventing dengue hemorrhagic fever. It can be concluded that the family's attitude in the category is good in preventing dengue hemorrhagic fever disease. The recommendation of health workers can come directly to the community to provide counselling on how to eradicate mosquito larvae and mosquito nests in the living environment and carry out individual hygiene.